GOOD CORPORATE GOVERNANCE DALAM ISLAM - Evan Hamzah (STAI Asy-Syukriyyah, 2014)
Simply put good corporate governance is defined as a good corporate governance to enhance the business success by taking into account the interests of stakeholders. Good corporate governance is composed of five principles, namely transparency, accountability, responsibility, independence, and fairness. Good corporate governance is a key to success for growing and profitable company in the long term as well as winning the global business competition, especially for companies that have been able to grow and has gone public. The concept of universal good corporate governance is closely associated with the teachings of Islam. Moral dimension of the implementation of good corporate governance, among others, lies in the principle of accountability (accountability), the principle of accountability (responsibility), the principle of openness (transparency) and fairness (fairness).